(Foundation-)Matrix Reloaded—Some Remarks on a Useful Concept and Its Pitfalls. (September 2014) - Scholz, Regine
In a preliminary remark those brilliant—mostly Jewish–German speaking intellectuals of the 20th-century in central Europe are acknowledged, who formed the background—the matrix—from which Foulkes developed his ideas of matrix and foundation matrix. After recalling the definition and summarizing the notion of foundation matrix, this concept is discussed, comparing it to other theories that aim at large scale transpersonal processes, namely the 'social unconscious' and 'large group identity'. The article closes pleading for very precise group analytic thinking, advising against the possibility that the concepts—if their process character is neglected—could be used to underpin a right wing/fascist argument.